2009
DOI: 10.1007/s00216-009-3249-z
|View full text |Cite
|
Sign up to set email alerts
|

Toxicities of nano zinc oxide to five marine organisms: influences of aggregate size and ion solubility

Abstract: Nano zinc oxide (nZnO) is increasingly used in sunscreen products, with high potential of being released directly into marine environments. This study primarily aimed to characterize the aggregate size and solubility of nZnO and bulk ZnO, and to assess their toxicities towards five selected marine organisms. Chemical characterization showed that nZnO formed larger aggregates in seawater than ZnO, while nZnO had a higher solubility in seawater (3.7 mg L(-1)) than that of ZnO (1.6 mg L(-1)). Acute tests were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
213
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 368 publications
(227 citation statements)
references
References 47 publications
10
213
1
3
Order By: Relevance
“…The size of the aggregates of the bulk material was lower (859-1564 nm). Our results are in close agreement with those of Wong et al (2010) who found that ZnO NPs tended to form aggregates in the micrometre range (2.3 ± 1.6 mm) in seawater, and these aggregates were bigger than those formed by its bulk counterpart (1.7 ± 1.2 mm). By contrast, in the study of Hsiao and Huang (2011) using ZnO NPs prepared by a precipitation or a solvothermal method, the smaller-sized ZnO particles aggregated to smaller secondary sizes than the larger NPs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The size of the aggregates of the bulk material was lower (859-1564 nm). Our results are in close agreement with those of Wong et al (2010) who found that ZnO NPs tended to form aggregates in the micrometre range (2.3 ± 1.6 mm) in seawater, and these aggregates were bigger than those formed by its bulk counterpart (1.7 ± 1.2 mm). By contrast, in the study of Hsiao and Huang (2011) using ZnO NPs prepared by a precipitation or a solvothermal method, the smaller-sized ZnO particles aggregated to smaller secondary sizes than the larger NPs.…”
Section: Discussionsupporting
confidence: 93%
“…It has also been described that ZnO NPs can dissolve into Zn ions. The solubility of ZnO in aqueous media can show important variations ranging from 3.7 mg/ml in seawater (Wong et al 2010) to 5.8-7.2 mg/ml in serum-free DMEM medium (Hsiao et al 2011) and up to 15 mg/ml in complete DMEM medium (Xia et al 2008). Since some Zn ions can be released into solution from the particles, a controversy surrounding the role played by these ions on toxicity remains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations